Human chromosome segregation involves multi-layered regulation of separase by the peptidyl-prolyl-isomerase Pin1 - Hellmuth, Susanne; Rata, Scott; Brown, Andreas; Heidmann, Stefan; Novak, Bela; Stemmann, Olaf (Molecular cell, 2015)
Ring shaped cohesin keeps sister chromatids paired until cleavage of its Scc1/Rad21 subunit by separase triggers chromosome segregation in anaphase. Vertebrate separase is held inactive by mutually exclusive binding to securin or Cdk1-cyclin B1 and becomes unleashed only upon ubiquitin dependent degradation of these regulators. Although most separase is usually found in association with securin, this anaphase inhibitor is dispensable for murine life while Cdk1-cyclin B1 dependent control of separase is essential. Here, we show that securin independent inhibition of separase by Cdk1-cyclin B1 in early mitosis requires the phosphorylation specific peptidyl-prolyl cis/trans isomerase Pin1. Furthermore, isomerization of previously securin bound separase at the metaphase-to-anaphase transition renders it resistant to re-inhibition by residual securin. At the same time, isomerization also limits the half-life of separase's proteolytic activity, explaining how cohesin can be reloaded onto telophase chromatin in the absence of securin and cyclin B1 without being cleaved. [Display omitted] •Separase is subject to native-state cis/trans isomerization by Pin1•Once liberated, separase is rendered resistant to remaining securin by Pin1•When securin is limiting, Pin1 is required for control of separase by Cdk1-cyclin B1•Isomerization limits the half-life of separase's proteolytic activity in late mitosis